Coal Gangue Ecological Matrix Coupled with Microalgae for Soil Improvement and Plant Growth in Reclaimed Mining Areas - Shuyu Yu; Jinning Li; Dandan Du; Hao Li; Jiayong Hao; Zedong Teng; Xiang Ji (Biology)
Coal gangue, a primary byproduct of coal mining, causes significant environmental harm due to its improper utilization. This research proposes integrating microalgae with coal gangue-derived ecological products to improve soil conditions in ecologically vulnerable coal-mining regions. A field-scale experiment at the Jintong Coal Mine tested soils amended with varying proportions of a coal gangue ecological matrix (0%, 10%, 30%, and 50%), with and without microalgae inoculation. The results demonstrated that coal gangue addition caused undesirable soil pH decreases (11.30~42.20%) while increasing total dissolved solids (506.88~524.93%) and organic matter (8.51~46.81%). These effects were mitigated by the presence of microalgae. Microalgae play a role in regulating soil nutrient profiles, enhancing enzymatic activities, and modulating the microbial community structure. For example, they restored catalase activity under the stress imposed by coal gangue and stimulated urease activity at higher coal gangue proportions. Plant growth trials revealed that adding 30% coal gangue or combining coal gangue with microalgae significantly promoted the growth of Medicago sativa L. In summary, coupling the coal gangue ecological matrix with microalgae effectively enhances soil quality. Maintaining the coal gangue addition at 30% or less in conjunction with microalgae application represents an optimal approach for soil improvement in mining areas.